STUDI LITERATUR : TRADISI LISAN SEBAGAI NILAI BUDAYA KEBERAGAMAN DI BERBAGAI DAERAH INDONESIA - Titih Nursugiharti; Rohim (Prosiding Seminar Nasional Indonesia, 2024)
One of the importance of oral traditions for human civilization is the formation of the character of a nation. The purpose of this writing is to look at Literary Studies: Oral Traditions as Cultural Values of Diversity in various regions of Indonesia. The research approach used is descriptive, analytical and critical. As a result, the author was able to thoroughly explain the value of oral traditions as cultural assets in various regions in Indonesia. The author made good use of two relevant data sources in this research, namely primary and secondary data sources. Books and scientific journals related to oral traditions are the main sources for this research. The results of this oral tradition research are part of the customs and culture that Indonesia has, namely relating to the habits of society towards other communities in establishing direct communication with their environment. This is considered the most important because this oral tradition contains many values embedded in it.